Neuropsychological Profiles of Three Subtypes of Impulsivity in the General Population: A Young Adults Study - Mario Rodolfo Squillace Louhau; Jimena Picón-Janeiro; Nicolás Mazzei; Alejandra Villar; Susana Azzollini (International Journal of Psychological Research, 2019)
The impulsivity construct has been investigated in the psychological literature as both a personality factor and a manifestation of the cognitive functioning of individuals. In addition, an increasing number of studies have shown that impulsivity is not a unitary concept and that it must be conceived of as several subtypes. We investigated whether a self-report test of three types of impulsivity could be a good predictor of cognitive functioning in healthy individuals. The sample was composed of 230 subjects (65% women) with a mean age of 28.4 years (SD = 13.6 years) from the general population of the Autonomous City of Buenos Aires, Argentina. The sample was evaluated using the Questionnaire on Compulsive Urgency, Sensation Seeking, and Impulsive Improvidence (CUBI-18; Squillace Louhau, & Picón Janerio, 2019), which measures three impulsivity subtypes. A battery of neuropsychological tests was administered to measure not only executive-attentional functioning, verbal and non-verbal fluency, and speed of processing, but also strategies in the decision-making process. The results showed a differential profile of the three subtypes of impulsivity. Compulsive Urgency was associated with greater executive- attentional difficulties, Impulsive Improvidence with lower fluency in processing nonverbal information, and Sensation Seeking with better general cognitive performance and risk-taking during decision-making.